S100A4 regulates macrophage invasion by distinct myosin-dependent and myosin-independent mechanisms - Dulyaninova, Natalya G. (Mol Biol Cell, 2018)
S100A4, a member of the S100 family of Ca(2+)-binding proteins, is a key regulator of cell migration and invasion. Our previous studies showed that bone marrow–derived macrophages from S100A4(−/−) mice exhibit defects in directional motility and chemotaxis in vitro and reduced recruitment to sites of inflammation in vivo. We now show that the loss of S100A4 produces two mechanistically distinct phenotypes with regard to macrophage invasion: a defect in matrix degradation, due to a disruption of podosome rosettes caused by myosin-IIA overassembly, and a myosin-independent increase in microtubule acetylation, which increases podosome rosette stability and is sufficient to inhibit macrophage invasion. Our studies point to S100A4 as a critical regulator of matrix degradation, whose actions converge on the dynamics and degradative functions of podosome rosettes.